Secondary Metabolites of Trichoderma sp. as Antifungal Against Rice Seed-borne Pathogen Fungi - Amalia, Anisa Rizki; Purnawati, Arika; Prasetyawati, Endang Triwahyu; Yanti, Vika (Universitas Labuhanbatu, 2023)
The use of quality seeds is necessary to increase rice productivity. The existence of pathogenic fungi infections causes the quality of rice seeds to decrease and impacts the ability to grow plants. Trichoderma sp. is known to produce secondary metabolites that can inhibit the growth of pathogens. This study aimed to examine the ability of the secondary metabolites of Trichoderma sp. at various concentration levels and immersion time to suppress pathogenic fungi infections carrying rice seeds. The research was carried out by giving seed immersion treatment. Then identify the pathogenic fungi the seeds carry for further testing with the blotter test method. The parameters tested were infection rate, infection suppression, and seed viability. The identification results showed types of pathogenic fungi carried by rice seeds included Fusarium sp., Alternaria sp., Aspergillus sp. Penicillium sp., and Rhizopus sp. Research also shows that the secondary metabolites of Trichoderma sp. are effective in improving the quality of rice seeds. The test results showed that the secondary metabolites of Trichoderma sp. can suppress the level of pathogenic fungi infection. There was no interaction between the treatment of metabolite concentrations and immersion time on all test parameters. Seed immersion treatment with secondary metabolites in the 5-20% concentration range has effectively reduced fungi infection rates and increased seed viability. Meanwhile, various levels of soaking time did not affect reducing the level of fungi infection but instead affected the viability of the rice seeds.